THE DECONSTRUCTION OF GENRE IN THE BOOK OF JONAH: TOWARDS A THEOLOGICAL DISCOURSE - Elata-Alster, Gerda (Literature and theology, 1989)
Gerda Elata-Alster, Rachel Salmon; THE DECONSTRUCTION OF GENRE IN THE BOOK OF JONAH: TOWARDS A THEOLOGICAL DISCOURSE, Literature and Theology, Volume 3, Issue 1